2009
DOI: 10.1262/jrd.20216
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Acrosomal Membrane from Sperm Head Improves Development of Rat Zygotes Derived from Intracytoplasmic Sperm Injection

Abstract: Abstract. When intracytoplasmic sperm injection (ICSI) is applied in the rat, sperm chromatin is introduced into the oocyte together with the acrosome, which does not enter the cytoplasm of the oocyte during normal fertilization, resulting in the rat giving birth to pups. Since successful ICSI was reported in rats, but with low efficiency, it has been observed that the acrosome of the sperm head seems to have detrimental effects on the embryonic development of ICSI oocytes. To improve ICSI in rats, the effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 36 publications
3
30
2
Order By: Relevance
“…While injection of uncapacitated spermatozoa with intact acrosomes affects development of mouse ICSI embryos [7], simultaneous removal of the plasma membrane and acrosome before ICSI improves embryonic development [8]. Supportive evidence has been presented for the rat [9].…”
Section: Introductionmentioning
confidence: 97%
“…While injection of uncapacitated spermatozoa with intact acrosomes affects development of mouse ICSI embryos [7], simultaneous removal of the plasma membrane and acrosome before ICSI improves embryonic development [8]. Supportive evidence has been presented for the rat [9].…”
Section: Introductionmentioning
confidence: 97%
“…2b). Similarly,in homologous rat ICSI, the timing of pronuclear formation using TX or lysolecithin treated sperm was significantly accelerated compared to control sperm [25]. In the mouse, homologous ICSI of TX treated sperm yielded no difference in fertilization, blastocyst, implantation and live birth rates compared to control sperm [36].…”
Section: Discussionmentioning
confidence: 93%
“…Regardless, live offspring have been born using ICSI in a variety of species, including humans and mice [23]. However, existing reports on higher incidence of chromosome aberrations [24] and lower developmental potentials [25,26] in embryos produced by ICSI indicate that further evaluations on the effects of the incorporation of the acrosome into the oocyte are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports showed higher efficiency in mouse and human ICSI following removal of the acrosomal vesicle [18,29,32], which rested on the assumption that its hydrolytic enzymes could harm the oocytes [25,37]. Notwithstanding that ionomycin induces acrosomal reaction (as suggested by Rotem et al [26] and confirmed in our experiments), we reached the same blastocyst rate by injecting piezo-pulsed spermatozoa pretreated both with and without ionomycin (PPS: 15.6 % vs. PPS-I: 15.5 %).…”
Section: Discussionmentioning
confidence: 99%